Sphagnum fuscum Growth and N Concentration in an Alberta Peatland Subjected to Increasing Nitrogen Deposition, 2011-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). Data collected of the growing season using the crank wire method allowed for the calculation of NPP. Tissues were also collected and analyzed on Leco TruSpec CN analyzer. Increasing N addition had no effect on Sphagnum fuscum NPP in year 1, but inhibited S. fuscum NPP in years 2-5, with capitula N concentrations remaining consistent across all years, but with stem N concentrations increasing with N input. The decrease in S. fuscum NPP with increasing N addition that we report for Mariana Lakes Bog has implications for peat accumulation in bogs.